School Transit and Accessing Public School in Detroit. Issue 6 (July 2022) - Pogodzinski, Ben; Lenhoff, Sarah Winchell; Cook, Walter; Singer, Jeremy
Students in the Detroit Public Community Schools District (DPSCD) have the highest rate of chronic absence (missing 10% or more of school days) among large districts in the United States. Additionally, students in DPSCD are among the poorest students in the country, often lacking access to reliable personal transportation or public transit to facilitate getting to school. Although DPSCD offers school-sponsored transit, only 30% of K-8 students were eligible for such transit in 2018 to 2019. Through the use of multilevel modeling, we sought to identify the association between eligibility for school-sponsored transit and attendance. Our findings indicated that there was a negative association of small magnitude between eligibility for school sponsored transit and school attendance. This counterintuitive finding may highlight the fact that transit eligibility is not sufficient to mediate the negative relationship between student poverty and attendance, and transit eligibility does not guarantee regular use of school-sponsored transit.